Nitrogen fertilization in pangola (Digitaria eriantha S.) grass under different sowing densities - Antonio-Medina, Anadelia (Ecosistemas y Recursos Agropecuarios, 2024)
The implementations of agricultural practices increase the yields, quality and nutritional content of grasses that are essential to satisfy animal food demand. The objective was to evaluate the performance and chemical composition of pangola grass, low planting densities (DS) and different levels of nitrogen fertilization (DFN), in acidic soils. A 3 x 5 factorial arrangement was initiated in divided plots; with three repetitions. Large plot DS: 1 500, 2 000, 2 500 kg MV ha-1 and small plot DFN levels: 0, 50, 100, 208, 300 kg N ha-1. Variables were evaluated: harvest [plant height (ALT), green forage kg (PV), dry forage g, kg and t (MSg, MSkg, MSt) and a proximal analysis: [ash (Cnz), humidity (Hum), extract ethereal (EE), crude protein (CP), neutral and acid detergent fibers (NDF, FDA), silica (SI) and acid detergent lignin (LDA)]. An analysis of variance, Tukey mean tests (α £0.05) and a multiple regression analysis were carried out with SAS software. The highest DM yields (5.6 t ha-1) in DS2500 kg MV ha-1 and DFN208-300 kg N ha-1. The CP content increased in DS2500 kg MV ha-1 and DFN208 kg N ha-1, while EE was higher in DFN100 kg N ha-1. It is concluded that the combination of DS2500 kg MV ha-1 and DFN208 kg N ha-1 improves the yield and nutritional quality of pangola grass in acidic soils.